Racial and ethnic disparities in longitudinal trajectories of cardiovascular risk factors in U.S. middle-aged and older adults - Matthew E. Dupre; Radha Dhingra; Hanzhang Xu; Scott M. Lynch; Qing Yang; Cassie Ford; Michael D. Green; Ying Xian; Ann Marie Navar; Eric D. Peterson (PLoS ONE, 2025)
Background Racial and ethnic disparities in cardiovascular disease (CVD) risk factors are well-documented. However, racial and ethnic differences in the longitudinal changes among multiple CVD risk factors are unknown. Methods We used prospective cohort data of U.S. adults aged ≥50 in the 2006–2016 Health and Retirement Study. Group-based multi-trajectory models characterized age-related trajectories of systolic blood pressure ([BP] mmHg), non-HDL cholesterol (mg/dL), diabetes mellitus (DM), and smoking. Racial and ethnic differences in the multi-trajectory profiles were examined using multinomial logistic regression. Karlson-Holm-Breen methods were used to assess factors contributing to these associations. Results Among 10,292 participants (median age: 61), approximately 32% had an overall favorable profile of CVD risk factors. Compared with non-Hispanic White adults, non-Hispanic Black adults were more likely to exhibit elevated systolic BP with high risks of DM (relative risk ratio [RRR] = 3.36; 95% CI, 2.69–4.21; P < .001) and with low risks of DM (RRR = 3.23; 95% CI, 2.38–4.38; P < .001). Non-Hispanic Black adults were also more likely to exhibit high rates of smoking with and without other co-occurring risk factors. Hispanic adults were most likely to exhibit high risks of DM with elevated systolic BP (RRR = 1.74; 95% CI, 1.28–2.38; P < .001) and without elevated systolic BP (RRR = 1.90; 95% CI, 1.50–2.40; P < .001). Education, income, and country-of-origin were significantly associated with the excess CVD risks observed among racial and ethnic minority groups. Conclusions Significant racial and ethnic disparities were observed in trajectories of CVD risk factors in U.S. adults. Social determinants largely contributed to these associations in non-Hispanic Black adults and Hispanic adults.